Comparative gene expression profile and DNA methylation status in diabetic patients of Kazak and Han people. Issue 36 (September 2018) - Wang, Cuizhe; Ha, Xiaodan; Li, Wei; Xu, Peng; Zhang, Zhiwei; Wang, Tingting; Li, Jun; Wang, Yan; Li, Siyuan; Xie, Jianxin; Zhang, Jun
Abstract : Abstract: We attempted to investigate the mechanism and susceptibility genes for diabetes in Han and Kazak ethnic individuals. The abdominal omental adipose tissues were obtained from diabetic cases and healthy controls. The gene expression and methylation data were produced for Kazak and Han individuals, respectively, and analyzed by bioinformatics analysis. We obtained 921 differentially expressed genes (DEGs) in Han group and 1772 in Kazak group. DEGs in Han group were significantly related with type 2 diabetes mellitus, and biosynthesis of amino acids, while the DEGs specific to Kazak patients were significantly enriched in metabolism-related pathways such as carbon metabolism, propanoate metabolism, and 2-oxocarboxylic acid metabolism. Major facilitator superfamily domain containing 1 ( MFSD1 ) was found to be a methylation associated gene at hypermethylation site of cg16289538 in Han group. Rho guanine nucleotide exchange factor 1 ( ARHGEF1 ) was the susceptible gene corresponding to the methylation sites of cg18800192 and cg00759295 in Kazak group. ARHGEF1 was also a node in protein–protein interaction network and significantly enriched in hsa04270: vascular smooth muscle contraction pathways. The molecular mechanism of diabetes may be different in Han and Kazak patients. MFSD1 and ARHGEF1 may be the diabetes susceptible genes. Abstract : Supplemental Digital Content is available in the text